السياحة البيئية كآلية لدعم تحقيق تنمية سياحية مستدامة - ايضاءات على بعض التجارب العربية - بوعكريف, زهير; بوحبيلة, الهام (جامعة الوادي- University of Eloued, 2016)
إن السياحة البيئية ذات التوازن البيئي ظاهرة جديدة تستوجب وتهدف إلى البحث والدراسة والتأمل في الطبيعة والنباتات والحيوانات وتوفير الراحة للإنسان، فالميزة التي يتيحها تطبيق السياحة البيئية هي ربط الاستثمار والمشاريع الإنتاجية للمجتمع المحلي مع حماية البيئة والتنوع الحيوي والثقافي للمناطق السياحية، وفق معادلة تنموية واحدة وذلك عن طريق إعداد برامج سياحية تعتمد على توجيه السياحة نحو المواقع المتميزة بيئيا مع التأكيد على ممارسة سلوكيات إبداعية ومسلية دون المساس بنوعية البيئة أو التأثير عليها. حيث أن هذا النمط الجديد من السياحية يكتسي أهمية بالغة بالنسبة لدول جنوب المتوسط -وفي مقدمتها الجزائر- التي تتوفر على مقومات طبيعية متميزة يجب استغلالها عن طريق دعم الحكومات بالتعاون مع القطاع الخاص بالتوجه إلى تشجيع السياحة البيئية التي تعمد إلى الحفاظ على التوازن البيئي وإحياء الموروث الثقافي والحضاري ودعم التنمية السياحية المستدامة في المناطق الريفية والصحراوية من أجل تنمية اقتصادية شاملة، كما هو الحال بالنسبة للمحميات الطبيعية التي أنشأت في بلدان سياحية مختلفة والتي أصبحت من أهم آليات ودعائم التطوير السياحي المستدام. The eco-tourism with ecological balance is a new phenomenon aims to research and study of nature , plants and animals and to provide human comfort , prime advantage offered by the application of eco-tourism is to link investment and production projects for the local community while protecting the environment and biodiversity, cultural, tourist areas, according to the equation developmental one and done through the preparation of tourist programs rely on direct tourism towards ecologically distinct sites with an emphasis on exercise behaviors creative and entertaining without compromising the quality of the environment or to influence them . As this new type of tourism is of paramount importance for the countries of the southern Mediterranean - At the forefront of Algeria - which are available on the elements of a normal premium that should be exploited by supporting governments in collaboration with the private sector to go to the promotion of eco-tourism , which deliberately to maintain the ecological balance and the revival of cultural heritage and cultural and support sustainable tourism development in rural and desert areas for the development of a comprehensive economic , as is the case for natural reserves established in different countries in which tourism has become one of the most important mechanisms of the pillars of sustainable tourism developmnt
Eco-tourism as a mechanism to support the achievement of sustainable tourism development
مقال
Keywords: السياحة البيئية - تنمية - مستدامة .